Program Pembelajaran Individual: Meningkatkan Keterampilan Mengancingkan Baju pada Anak Disabilitas Intelektual Sedang - Lestari, Dita; Andayani, Budi (Al-Athfal: Jurnal Pendidikan Anak, 2020)
This study aims to observe the effectiveness of Individual Learning Program on improving shirt-buttoning skills among children with moderate intellectual disabilities. This study hypothesizes that the students' ability to button their shirts improved after applying the Individual Learning Program approach to the chaining learning method. The participants of this study were four students with moderate intellectual disabilities ranging in age from 10-12 years. The four participants were selected based on interviews with the homeroom teacher and parents as well as observations that showed that participants had low skills in buttoning up their clothes. This research is a quasi-experimental study with a single subject research design in which data analysis uses descriptive statistical analysis consisting of two steps: (1) analysis in two conditions and (2) analysis between conditions. This study's data were analyzed using visual image data analysis techniques. The results showed that the Individual Learning Program with chaining learning strategies, both backward and forward, and the total task presentation could effectively improve buttoning skills in children with intellectual disabilities.